The impact of typological similarities and differences between German and Italian on the acquisition of language-specific phonetic cues in bilingual children: insights from the T-complex - Bloder, Theresa; Shinohara, Yasuaki; Rinker, Tanja; Shafer, Valerie L. (Frontiers in Human Neuroscience, 2024)
IntroductionLateral temporal neural measures (Na and T-complex Ta and Tb) of the auditory evoked potential (AEP) index auditory/speech processing and have been observed in children and adults. While Na is already present in children under 4 years of age, Ta emerges from 4 years of age, and Tb appears even later. The T-complex has been found to be sensitive to language experience in Spanish-English and Turkish-German children and adults. In particular, Ta elicited to a vowel has been found to be sensitive to language experience in bilingual preschool children. This paper examines neural responses in 4-to-6-year-old Italian-German bilingual and German monolingual children using language-specific phonetic cues for voicing.MethodsWe tested children's processing of voicing features in bilabial stop consonants in relation to (1) their language status (i.e., being monolingual vs. bilingual) as well as to (2) their relative amount of current exposure to the heritage (Italian) and the societal language (German). Italian-German bilingual and German monolingual children were hypothesized to encode the temporal properties of a set of Voice Onset Time (VOT) stimuli differently as indexed by Ta and Tb.ResultsThe results revealed no main effects of language group, but interactions of group with hemisphere and stimulus. In particular, bilingual children showed less hemispheric differentiation and an attenuated (less positive) response at the right site (T8) for the 0 ms VOT stimulus during the Ta-Tb time window. Children with more German (and consequently, less Italian) input showed a more positive T8 response for the Na, Ta and Tb time intervals.DiscussionThese findings partially replicated previous studies, but also revealed that stimulus factors modulate the response. They suggest that a delay in commitment is found only in bilinguals with less input in the target language, and those who are strongly dominant in one of the two languages will resemble monolinguals in the development of T-complex responses. However, the finding of greater Na positivity for German-dominant bilinguals suggests that their specific experience also influences processing, but perhaps via a different mechanism than found for the more balanced bilinguals.